The micro-layered fast-neutron detector - Ghosh, Priyarshini (Kansas State University, 2021)
The Micro-Layered Fast-Neutron Detector (MLFD) is a novel fast-neutron detection technology that has been developed from concept stage to demonstrable functionality in a laboratory environment. The MLFD boasts a high fast-neutron detection efficiency of 9.2% at 43 mm length-of-detector, a near-100% gamma-ray rejection capability without requiring pulse shape discrimination or any additional electronics or techniques, and suppression of Ĉerenkov radiation generation inherently by design. These features have been achieved by careful material selection in suitable geometrical fashion. Polymethyl methacrylate (PMMA) was used as a neutron converter (by proton recoil) and light guide, and zinc sulfide as an inorganic scintillator, in an alternating layer configuration such as to maximize scintillation photon collection from neutron interactions while minimizing Ĉerenkov generation. A photodetector attaches to the side of the MLFD, which can either be a photomultiplier tube (PMT) or a silicon photomultiplier (SiPM), depending on the application desired. The orientation of the photodetector on the side (parallel to the longest length of the MLFD) also reduces probability of forward-propagational Ĉerenkov photons from being collected. The detection efficiency can also be scaled by simply increasing the number of layers, i.e., the length of the detector. The vastly different decay pulse times for protons (700 ns to 10,000 ns) and electrons (12 ns) leads to a very distinct neutron and gamma-ray event separation, leading to a PSD ratio of 4.56. Furthermore, replacing the PMT with SiPMs reduces the Ĉerenkov radiation developed in the PMT photocathode window, thereby eliminating the need for pulse shape discrimination altogether, and only requires a low LLD to reject almost all gamma radiation. Although originally designed for use at the TREAT facility of Idaho National Laboratory, the MLFD has exhibited performance that makes it versatile for extended application in SNM searches. Therefore, the MLFDs were coupled to an array of SiPMs as an imager to locate the direction of a neutron source in a mixed radiation environment, and was successfully able to predict the location within 30 seconds in a 5cm radius. The imaging system can be configured to have all necessary electronics on-board, making it light-weight, portable and compact. The MLFD can be batch-fabricated with ease and in a simple four-step process using commonly-found laboratory equipment.
Keywords: Scintillator; Cerenkov rejection; Gamma-ray rejection; Proton recoil detector; Fast neutron detector; Inorganic crystal scintillator